Development of orthorexia nervosa in academics in modern society (Research, Society and Development, 2021)
This work aimed to identify factors that trigger orthorexia nervosa, regarding eating disorders, in academics in modern society. To accomplish this  the study consisted of a review based on the analysis of articles from 2010 to 2020, in English, Portuguese and  Spanish, obtained  from the databases Pubmed, Scielo, Bvs, LILACS and Bireme. From the data analysis, it was found that Orthorexia nervosa (ON) is more frequent in the population of young academics in health courses and health professionals, emphasizing that it also affects individuals who are extremely concerned with physical image. It was concluded that the identification of Orthorexia is extremely important to prevent and treat possible pathological conditions that may arise during the development of orthorexia nervosa regarding eating disorders. Nutritional and psychological monitoring is required for individuals diagnosed with this eating disorder. As it is a recent disorder, further studies are needed, covering orthorexia in a thorough and thorough manner.